Faktor-Faktor Yang Dapat Mempengaruhi Perilaku Menabung Mahasiswa Era Pandemi Covid 2019 - Eva Karla; Stevianus Stevianus (Journal on Education, 2023)
In the era of the COVID-19 pandemic, saving activities are becoming increasingly important for students as a strategy in dealing with future economic uncertainties. However, there are several factors that can influence student saving behavior during this pandemic. Some of these factors include the influence of financial conditions, the level of closeness with family, access to technology, and psychological factors. During the COVID-19 pandemic, students around the world are facing increasing economic uncertainty. Therefore, saving is an important strategy for students in facing an uncertain future. However, various factors such as financial conditions, relationships with family, access to technology, and psychological factors can influence student saving behavior. This requires extra attention from educational institutions and financial institutions in providing the necessary education and support for students in facing economic challenges during the COVID-19 pandemic. The research method used is the literature method by conducting a literature search that is relevant to the research topic using sources such as online databases, journals, books, articles, and other publications. That the factors influencing student saving behavior during the COVID-19 pandemic may vary, such as personal financial conditions, general economic stability, the influence of family and friends, and lifestyle changes that have occurred as a result of the pandemic.